2017
DOI: 10.30918/ampr.54.17.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adenanthera pavonina leaves extracts and β- sito sterol glucoside in CCl4 induced hepatocellular injury in Wistar rats

Abstract: The aim of this research work was to investigate the less toxic and more specific hepatoprotective and antioxidant effects of hexane, ethanol extracts along with pure compound β-sitosterol glucoside isolated from leaves of Adenanthera pavonina in carbon tetra chloride (CCl 4 ) induced liver damage in rat. The anti-oxidant effect was assessed in different concentrations of 100, 250, 500 and 1000 µg/ml by in-vitro model system of ferric cyanide reducing power assay using, ascorbic acid as a standard drug. Ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Bergenin isolated from the cortex of M. japonicus exhibited a hepatoprotective effect in rats (IC 50 of 50 mg/kg) and normalized the decreased activities of glutathione S-transferase and glutathione reductase, in addition to significantly preventing the elevation of hepatic malondialdehyde formation and depletion of reduced glutathione content in the liver [ 206 ]. Bergenin isolated from the herb S. stolonifera exhibited (IC 50 of 100 mg/kg) a hepatoprotective effect and detoxified liver cells [ 206 ]; bergenin isolated from the extract of P. pterocarpum showed a hepatoprotective effect in albino rats (IC 50 of 100 mg/kg) reducing excessive levels of the enzymes alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma-glutamyltransferase (γ-GT), direct bilirubin (DB) and total bilirubin (TB) [ 207 , 208 ]; bergenin and 11- O- galloylbergenin, isolated from the leaves of A. edulis , have remarkable antihepatotoxic activity against CCl 4 and galactosamine cytotoxicity in cultured primary rat hepatocytes (IC 50 of 100 mg/kg) [ 122 ]. Mondal et al [ 209 ] reported that the hepatoprotective capacity of bergenin could also be related to the fact that it can sequester free radicals and restore the antioxidant oxidant balance.…”
Section: Biological and Pharmacological Activities Of Bergeninmentioning
confidence: 99%
“…Bergenin isolated from the cortex of M. japonicus exhibited a hepatoprotective effect in rats (IC 50 of 50 mg/kg) and normalized the decreased activities of glutathione S-transferase and glutathione reductase, in addition to significantly preventing the elevation of hepatic malondialdehyde formation and depletion of reduced glutathione content in the liver [ 206 ]. Bergenin isolated from the herb S. stolonifera exhibited (IC 50 of 100 mg/kg) a hepatoprotective effect and detoxified liver cells [ 206 ]; bergenin isolated from the extract of P. pterocarpum showed a hepatoprotective effect in albino rats (IC 50 of 100 mg/kg) reducing excessive levels of the enzymes alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma-glutamyltransferase (γ-GT), direct bilirubin (DB) and total bilirubin (TB) [ 207 , 208 ]; bergenin and 11- O- galloylbergenin, isolated from the leaves of A. edulis , have remarkable antihepatotoxic activity against CCl 4 and galactosamine cytotoxicity in cultured primary rat hepatocytes (IC 50 of 100 mg/kg) [ 122 ]. Mondal et al [ 209 ] reported that the hepatoprotective capacity of bergenin could also be related to the fact that it can sequester free radicals and restore the antioxidant oxidant balance.…”
Section: Biological and Pharmacological Activities Of Bergeninmentioning
confidence: 99%
“…-glucopyranosyl-(6' 2' -2) --D-glucopyranosyl(6'' 1', 2 2)--D-glucopyranoside (71) , a few compounds showed potential pharmacological effects.β-sitosterol glucoside (4) was isolated from the leaves of A. pavonina and showed potential antioxidant and hepatoprotection ability against CCl4 induced liver injury rats[38]. In the investigation of antioxidant and (49) showed potential activity against Gram-positive and Gram-negative bacteria as well as radical scavenging power[33].…”
mentioning
confidence: 99%